A method for preparing lithium battery separator using Pickering emulsion polymerization
Through Pickering Lotion Jelly, the use of plant oil and nano -fiber filaments are used to prepare polymer composite emulsion to solve the problem of complexity and energy consumption of lithium battery septum during the charging and discharge process. Adhesive diaphragm performance.
Patent Information
- Application Number
- CN202410272498.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-03-11
AI Technical Summary
The existing lithium battery separators produce heat shrinkage during charging and discharging, which poses safety risks. The production process is complex and energy-consuming, and the coating stability affects the performance of the separator.
Pickering emulsion aggregates are used to prepare lithium battery diaphragm, and vegetable oils are used as raw materials to prepare Pickering emulsion, and combined with nano -fiber filaments and styrene monomers. On the base membrane.
It achieves high heat resistance and high adhesion of the lithium battery separator, simplifies the preparation process, reduces energy consumption and cost, and improves the stability of the coating.
Smart Images

Figure CN118165183B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a lithium battery separator by using Pickering emulsion polymerization, which is characterized by using vegetable oil to prepare the Pickering emulsion. Background Art
[0002] At present, commercial lithium batteries are mainly composed of four components: electrolyte, diaphragm, positive electrode and negative electrode. The diaphragm plays the role of blocking electrons between the positive and negative electrodes and transmitting lithium ions in lithium batteries. And ultimately has an important impact on the safety performance, capacity, and cycle of lithium-ion batteries. At present, polyethylene and polypropylene materials with microporous structures are commonly used for diaphragms, but the battery generates a lot of heat during the charging and discharging process, which causes the diaphragm to shrink greatly, posing a safety hazard. In order to improve the heat resistance of the diaphragm, ceramic powder or aramid materials are usually coated on the polyolefin base film, but inorganic particles are easy to fall off. In addition, the current battery preparation process requires that there is a strong adhesion between the diaphragm and the pole piece, and a (PVDF, PMMA) coating layer is usually coated on the ceramic layer diaphragm. At present, the coating material formula is usually composed of adhesives, dispersants, wetting agents, thickeners, etc. These components are mixed and stirred at high speed to prepare a coating slurry and then coated on the base film by a coater, but because there is no force between the internal structures of these components. As a result, the slurry after high-speed stirring is usually less stable, resulting in large fluctuations in coating thickness during the coating process, which ultimately affects the performance of the diaphragm. In addition, the existing heat-resistant layer and the adhesive layer are stacked on the base film in sequence, and the preparation process is relatively complex and energy-intensive.
[0003] Pickering emulsion is a new type of emulsion that uses solid particles to replace traditional organic surfactants to stabilize the emulsion system. Nanofibers are the most abundant natural polymers in nature and are widely found in various agricultural and forestry resources and their residues. Due to its excellent mechanical properties, thermal properties, good biocompatibility, and renewability, it has been used as a solid particle to prepare Pickering emulsions. Pickering emulsion polymerization has become one of the most important synthetic methods in the field of polymer science due to its green and environmental protection. The Pickering emulsion polymerization system mainly includes five main substances: emulsifier, initiator, reaction monomer, dispersion medium, and buffer. The high stability of Pickering emulsion polymerization has a wide range of applications in cosmetics, food industry, drug delivery, etc. Vegetable oils are mainly composed of glycerol and linear unsaturated fatty acids, which give them high reactivity. Vegetable oils can be converted into monofunctional monomers by cracking, catalytic hydrolysis, oxidation, and terminal functionalization, and further polymerized to obtain vegetable oil polymers. Vegetable oil polymers have many excellent properties, such as high stability, flexible and adjustable molecular structure, and high purity. At present, the process of preparing lithium battery separator adhesives usually uses suspension polymerization, which requires the use of large amounts of organic solvents and causes harm to the environment. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides an environmentally friendly and efficiently prepared lithium battery composite membrane, wherein the lithium battery membrane comprises a polyolefin base film and a mixed coating, wherein the outermost layer of the mixed coating is nanofibrils, the middle layer is a vegetable oil polymer with a low softening point, and the inner core is a hard segment polystyrene; the ratio of nanofibrils, vegetable oils and polystyrene is 0.1-2:75-95:4.9-23; the solid content of the nanofibrils is 0.1wt%-1wt%.
[0005] To achieve the above-mentioned object, the present invention provides a method for preparing a Pickering emulsion, comprising the following steps: (S1) preparing a plant oil-based acrylate monomer: (S11) mixing a plant oil, a neutralizer and a catalyst, heating the mixture to a first temperature and reacting the mixture for a first time to obtain a plant oil-based precursor; (S12) heating the plant oil-based precursor and an acid anhydride to a second temperature and reacting the mixture for a second time to obtain a plant oil-based acrylate monomer; and (S2) preparing a Pickering emulsion: (S21) mixing the plant oil-based acrylate monomer prepared in (S12), a styrene monomer and a nanofibril suspension to obtain an oil-water mixture, i.e., obtaining a Pickering emulsion.
[0006] Preferably, the method further comprises the following steps: (S22) treating the oil-water mixture obtained by stirring in (S21) for a third time in an ultrasonic wave of 600-800 W to obtain a Pickering emulsion; and (S23) deoxygenating the Pickering emulsion obtained in (S22) for 0.5-1 hour, adding a water-soluble initiator to set the third temperature for polymerization for a fourth time; after the reaction is completed, cooling to room temperature, filtering through a 100-300 mesh nylon filter to obtain a polymer composite emulsion.
[0007] Preferably, in (S11), the weight ratio of vegetable oil, neutralizer and catalyst is 10-40:1-6:0.1-2; the first temperature is 50-80°C; and the first time is at least 8 hours.
[0008] Preferably, in (S11), the vegetable oils include tung oil, rubber seed oil, olive oil, tung oil, castor oil, palm oil, soybean oil, linseed oil, linseed oil, sunflower oil, sunflower oil, coconut oil, cottonseed oil, safflower oil, safflower seed oil, tall oil, pine nut oil, rapeseed oil, corn oil, grape seed oil, peanut oil, hemp seed oil, perilla seed oil, poppy seed oil, sesame oil, canola oil, canola oil, algae oil, avocado oil, rice oil, shea butter, camellia oil, walnut oil, tomato seed oil, almond oil, apricot oil, cashew oil, nut oil, pistachio oil, walnut oil, nut oil, or any combination thereof; the neutralizer is N-methylethanolamine, triethylamine, diethylenetriamine, triethanolamine, or any combination thereof; the catalyst is sodium hydroxide, potassium hydroxide, sodium methoxide, catalytic ammonia water, or any combination thereof.
[0009] Preferably, in (S12), the weight ratio of the vegetable oil-based precursor to the acid anhydride is 10-40:4-25; the second temperature is 60-80° C.; and the second time is 8-12 hours.
[0010] Preferably, in (S21), the weight ratio of oil to water in the oil-water mixture is 1:(4-8), the nanofibers are cotton wool, pulp, wood pulp, hemp, or any combination thereof; the water-soluble initiator is ammonium persulfate, potassium persulfate, a metal salt of peroxide, or any combination thereof.
[0011] Preferably, in (S22), the weight ratio of the vegetable oil-based acrylate monomer, the styrene monomer and the nanofiber suspension is 10-40:1-10:40-400; and the third time is 10-15 minutes.
[0012] Preferably, in (S23), the weight ratio of the Pickering emulsion to the water-soluble initiator is 40-80:0.2-0.4; the third temperature is 60-80°C; the room temperature is 25-35°C; and the fourth time is 2-4 hours.
[0013] The present invention further provides a method for preparing a lithium battery separator using Pickering emulsion polymerization, comprising the following steps: (S3) Preparation of a lithium battery separator: (S31) Uniformly coating 1-3 parts of a Pickering emulsion on a base film to form a separator coating, drying the separator coating at a fourth temperature, and drying the separator for a fifth time to obtain a mixed-coating separator having heat resistance and adhesion, wherein the Pickering emulsion is prepared according to the method described above.
[0014] Preferably, in (S31), the fourth temperature is 50-70°C; the fifth time is 0.5-2 minutes; and the base film is a PP base film or a PE base film.
[0015] The beneficial effect of the present invention is to obtain a green, environmentally friendly and efficiently prepared lithium battery composite diaphragm. The preparation method is more environmentally friendly by synthesizing plant oil-based acrylate monomers using plant oil as raw materials, adding a certain proportion of styrene monomers, and carrying out Pickering emulsion polymerization using biomass raw material nanofibrils as stabilizers.
[0016] The prepared polymer emulsion is directly coated on the base film, which can make the coated film have excellent heat resistance and high adhesion. And the coating method only needs one coating to have these properties. Compared with the currently commonly used two-coating method, the final energy consumption and cost are greatly reduced. And the prepared polymer emulsion has high stability, which reduces the risk in the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figures 1 to 3 It is a preparation flow chart of the present invention.
[0018] Figure 4 Schematic diagram of polymer composite emulsion.
[0019] Figure 5 Schematic diagram of the lithium battery separator after coating with polymer composite emulsion.
[0020] Figure 6 It is a line chart of battery discharge test. DETAILED DESCRIPTION
[0021] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0022] See also Figures 1 to 3 The present invention provides a method for preparing a lithium battery separator by using Pickering emulsion polymerization, comprising the following steps:
[0023] (S1) Preparation of vegetable oil-based acrylate monomers:
[0024] (S11) Weigh 10-40 parts by weight of vegetable oil, 1-6 parts by weight of a neutralizer, and 0.1-2 parts by weight of a catalyst, seal and heat to 50-80° C. for reaction for 8 hours, remove unreacted substances and the catalyst, and obtain a vegetable oil-based precursor.
[0025] (S12) 10-40 parts by weight of the vegetable oil-based precursor and 4-25 parts by weight of anhydride obtained in (S11) are sealed and heated to 60-80° C. for reaction for 8-12 hours, and then unreacted products are removed to obtain a vegetable oil-based acrylate monomer.
[0026] (S2) Preparation of polymer composite emulsion:
[0027] (S21) Weigh 10-40 parts by weight of the plant oil-based acrylate monomer prepared in (S12), 1-10 parts by weight of styrene monomer, and 40-400 parts by weight of the nanofiber suspension, add the monomer mixture dropwise into the nanofiber suspension, stir evenly to obtain an oil-water mixture, and then treat it in a 600-800W ultrasonic crusher for a period of time to obtain a Pickering emulsion.
[0028] (S22) After nitrogen deoxygenation for 0.5-1 hour, 0.2-0.4 parts by weight of a water-soluble initiator is added to a thermostat set at 60-80° C. for polymerization for 2-4 hours; after the reaction is completed, the mixture is cooled to room temperature and filtered through a 100-300 mesh nylon filter to obtain a polymer composite emulsion ( Figure 4 ).
[0029] (S3) Preparation of lithium battery separator:
[0030] (S31) 1-3 parts by weight of the polymer composite emulsion (S22) is evenly coated on the base film by roller coating, and the above-mentioned diaphragm is placed in a blast oven at 50-70° C. for drying. After drying for 0.5-2 minutes, the diaphragm is a heat-resistant and adhesive mixed coating diaphragm ( Figure 5 ).
[0031] In some embodiments, the vegetable oil in (S11) includes tung oil, rubber seed oil, olive oil, tung oil, castor oil, palm oil, soybean oil, linseed oil, linseed oil, sunflower oil, sunflower oil, coconut oil, cottonseed oil, safflower oil, safflower seed oil, tall oil, pine nut oil, rapeseed oil, corn oil, grape seed oil, peanut oil, hemp seed oil, perilla seed oil, poppy seed oil, sesame oil, canola oil, canola oil, algae oil, avocado oil, rice oil, shea butter, camellia oil, walnut oil, tomato seed oil, almond oil, apricot oil, cashew oil, nut oil, pistachio oil, walnut oil, nut oil, or any combination thereof; the neutralizer is N-methylethanolamine, triethylamine, diethylenetriamine, triethanolamine, or any combination thereof; the catalyst is sodium hydroxide, potassium hydroxide, sodium methoxide, catalytic ammonia water, or any combination thereof.
[0032] In some embodiments, in (S21), the weight ratio of oil to water in the oil-water mixture is 1:(4-8), the nanofibers are cotton wool, pulp, wood pulp, hemp, or any combination thereof; the water-soluble initiator is ammonium persulfate, potassium persulfate, a metal salt of peroxide, or any combination thereof.
[0033] Embodiment 1:
[0034] The preparation method of the vegetable oil-based acrylate monomer specifically comprises the following steps:
[0035] (1) 30 parts of tung oil were weighed according to mass fraction, purged with nitrogen at 100°C for 30 min, cooled to 65°C, added with 6 parts of neutralizer, and then added with 0.7 parts of sodium methoxide solution (5 mol / L), sealed and reacted at 65°C for 8 h, and then dissolved in 30 parts of dichloromethane (DCM), washed with saturated sodium chloride, and dried over anhydrous magnesium sulfate to obtain a vegetable oil-based precursor.
[0036] (2) According to the mass fractions, 30 parts of the vegetable oil-based precursor obtained in step (1), 10 parts of acid anhydride, and 0.2 parts of 4-dimethylaminopyridine were sealed and heated to 65°C for reaction for 8 hours, then poured into 30 parts of dichloromethane (DCM) to dissolve, washed with saturated sodium bicarbonate and saturated sodium chloride respectively, dried with anhydrous magnesium sulfate, and then passed through an alkaline alumina column to obtain a vegetable oil-based acrylate monomer.
[0037] Embodiment 2:
[0038] (1) According to the weight ratio, 8 parts of the vegetable oil-based acrylate monomer in Example 1 and 2 parts of the styrene monomer were weighed, mixed and added dropwise to 80 parts of a 0.2 wt % nanofibril suspension. After being fully dispersed, the mixture was treated in an ultrasonic crusher with a power of 600 W for 10 min to obtain a Pickering emulsion 1. The stability, particle size and viscosity of the Pickering emulsion 1 are shown in Table 1.
[0039] (2) Weigh 30 parts by mass of the Pickering emulsion 1 in step (1) and place it in a 65°C constant temperature apparatus for deoxygenation by nitrogen for 30 minutes, then add 0.05 parts of a water-soluble initiator, potassium persulfate, and react for 3 hours. Then, raise the temperature to 80°C for reaction for 30 minutes, cool to room temperature, and filter through a 100-mesh nylon filter to remove the filter residue to obtain a polymer composite emulsion.
[0040] (3) Taking 5 parts by weight of the polymer emulsion prepared in step (2), evenly coating them on the PE base film using a laboratory small roller coater, and then baking them in an oven at 60° C. for 1 minute to obtain a novel lithium battery separator.
[0041] Embodiment 3:
[0042] (1) According to the weight percentage, 8 parts of the vegetable oil-based acrylate monomer in Example 1 and 2 parts of the styrene monomer were weighed, mixed and added dropwise to 40 parts of a 0.5 wt % nanofibril suspension. After being fully dispersed, the mixture was treated in an ultrasonic crusher with a power of 600 W for 10 min to obtain Pickering emulsion 2. The stability, particle size and viscosity of Pickering emulsion 2 are shown in Table 1.
[0043] (2) Weigh 30 parts by mass of the Pickering emulsion prepared in step (1), deoxygenate it in a 65°C constant temperature apparatus with nitrogen for 30 minutes, add 0.1 parts of a water-soluble initiator, potassium persulfate, and react for 3 hours. Then, raise the temperature to 80°C and react for 30 minutes. Then, cool the temperature to room temperature and filter it through a 100-mesh nylon filter to remove the residue, thereby obtaining a polymer composite emulsion.
[0044] (3) Taking 5 parts by weight of the polymer emulsion prepared in step (2), evenly coating them on the PE base film using a laboratory small roller coater, and then baking them in an oven at 60° C. for 1 minute to obtain a novel lithium battery separator.
[0045] Embodiment 4:
[0046] (1) According to the weight percentage, 8 parts of the vegetable oil-based acrylate monomer in Example 1 and 2 parts of the styrene monomer were weighed, mixed and added dropwise to 40 parts of 1.0 wt% nanofibril suspension. After being fully dispersed, the mixture was treated in an ultrasonic crusher with a power of 600 W for 10 min to obtain Pickering emulsion 3. The stability, particle size and viscosity of Pickering emulsion 3 are shown in Table 1.
[0047] (2) Weigh 30 parts by mass of the Pickering emulsion prepared in step (1), deoxygenate it in a constant temperature apparatus at 65°C for 30 minutes, add 0.15 parts of a water-soluble initiator, potassium persulfate, and react for 3 hours. Then, raise the temperature to 80°C for 30 minutes, cool it to room temperature, and filter it through a 100-mesh nylon filter to remove the residue, thereby obtaining a polymer composite emulsion.
[0048] (3) Taking 5 parts by weight of the polymer emulsion prepared in step (2), evenly coating them on the PE base film using a laboratory small roller coater, and then baking them in an oven at 60° C. for 1 minute to obtain a novel lithium battery separator.
[0049] Comparative Example 1:
[0050] (1) According to the weight percentage, 8 parts of the vegetable oil-based acrylate monomer in Example 1 and 2 parts of the styrene monomer were weighed, mixed and added dropwise to 40 parts of a 0.2 wt % nanofibril suspension. After being fully dispersed, the mixture was treated in an ultrasonic crusher with a power of 600 W for 10 min to obtain Pickering emulsion 4. The stability, particle size and viscosity of Pickering emulsion 4 are shown in Table 1.
[0051] (2) 30 parts by mass of the Pickering emulsion prepared in step (1) were weighed and deoxygenated in a constant temperature apparatus at 4 to 65° C. for 30 min. 0.05 parts of a water-soluble initiator, potassium persulfate, was added and reacted for 3 h. The temperature was raised to 80° C. for 30 min. The temperature was then lowered to room temperature and filtered through a 100-mesh nylon filter to remove the residue, thereby obtaining a polymer composite emulsion.
[0052] (3) Taking 5 parts by weight of the polymer emulsion prepared in step (2), uniformly coating them on the PE base film using a laboratory small roller coater, and then baking them in an oven at 60° C. for 2 minutes to obtain a novel lithium battery separator.
[0053] Comparative Example 2:
[0054] (1) According to the weight percentage, 8 parts of the vegetable oil-based acrylate monomer in Example 1 and 2 parts of the styrene monomer were weighed, mixed and added dropwise to 80 parts of a 0.1 wt % nanofibril suspension. After being fully dispersed, the mixture was treated in an ultrasonic crusher with a power of 600 W for 10 min to obtain Pickering emulsion 5. The stability, particle size and viscosity of Pickering emulsion 5 are shown in Table 1.
[0055] (2) Weigh 30 parts by mass of the Pickering emulsion prepared in step (1), deoxygenate with nitrogen in a thermostatic apparatus at 5 to 65° C. for 30 min, add 0.05 parts of a water-soluble initiator, potassium persulfate, and react for 3 h. Heat the mixture to 80° C. for 30 min, then cool the mixture to room temperature and filter through a 100-mesh nylon filter to remove the residue, thereby obtaining a polymer composite emulsion.
[0056] (3) Taking 5 parts by weight of the polymer emulsion prepared in step (2), uniformly coating them on the PE base film using a laboratory small roller coater, and then baking them in an oven at 60° C. for 2 minutes to obtain a novel lithium battery separator.
[0057] Table 1
[0058] CNFs concentration (wt%) Oil-water ratio Particle size distribution (nm) Stability (Y / N) Viscosity(Mpa*s) Example 2 0.2 1:8 800 Y 108.6 Example 3 0.5 1:4 200 / 1500 Y 926.3 Example 4 1.0 1:4 300 / 1800 Y 2041.8 Comparative Example 1 0.2 1:4 800 Y 372.5 Comparative Example 2 0.1 1:8 100 / 1000 N 91.7
[0059] Table 2
[0060]
[0061]
[0062] 1. The Pickering emulsions prepared in Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were subjected to performance tests, and their stability, particle size, viscosity and other parameters were statistically analyzed. The statistical test data are shown in Table 1, wherein stability refers to whether the Pickering emulsion of the nanofibril suspension and the styrene monomer and the vegetable oil-based acrylate monomer is stable after high-speed dispersion; and due to different proportions of the nanofibril suspension, the degree of coating of the Pickering emulsion is different, resulting in different particle size distributions.
[0063] 2. The performance of the new lithium battery separators prepared in Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 was tested, and the air permeability increase, internal resistance, thermal shrinkage rate and bonding strength data were statistically shown in Table 2.
[0064] 3. Battery test: The modified diaphragm in Example 2 was wound with the positive electrode sheet (positive electrode material is MCN523) and the negative electrode sheet (negative electrode material is graphite) to form a battery (the electrolyte is a ternary battery electrolyte), and then the discharge capacity test was carried out in the order of 55°C, 25°C, 0°C, -10°C, and -20°C. Before the test, the battery was fully charged at 25°C (the discharge cut-off voltage at -20°C was 2.5V, and the other temperatures were 3.0V). The change in battery capacity retention was recorded to evaluate the cycle stability of the modified diaphragm. Among them, the modified diaphragm in Example 1 was tested 7 times, and the results are as follows: Figure 6 As shown; battery testing shows that under the same temperature conditions, there is no significant difference in capacity retention rate.
[0065] From Table 1 and Table 2, it can be seen that when the concentration of the nanofiber suspension is 0.2wt% and the oil-water ratio is 1:8, the air permeability, internal resistance and thermal shrinkage of the modified diaphragm are reduced, and the bonding strength is improved. At higher temperatures, the battery capacity retention rate is better. In addition, due to the higher bonding strength, the required diaphragm can be prepared by reducing the number of coatings.
[0066] However, what is described above is only a preferred embodiment of the present invention, but it cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.
Claims
1. A method for preparing a Pickering emulsion, comprising the following steps: (S1) Preparation of vegetable oil-based acrylate monomers: (S11) mixing the vegetable oil, the neutralizer and the catalyst, heating to a first temperature and reacting for a first time to obtain a vegetable oil-based precursor; (S12) heating the vegetable oil-based precursor and the acid anhydride to a second temperature and reacting for a second time, Obtaining a vegetable oil-based acrylate monomer; and (S2) Pickering emulsion preparation: (S21) The plant oil-based acrylate monomer and styrene monomer prepared in (S12) are mixed and stirred with 0.2wt% to 1.0wt% of the nanofibril suspension to obtain an oil-water mixture, wherein the weight ratio of oil to water in the oil-water mixture is 1:(4-8), i.e., a Pickering emulsion is obtained.
2. The method according to claim 1, characterized in that: Before obtaining the Pickering emulsion, the method further comprises the following steps: (S22) treating the oil-water mixture obtained by stirring in (S21) in an ultrasonic wave of 600-800W for a third time to obtain a Pickering emulsion; and (S23) After deoxygenating the Pickering emulsion obtained in (S22) for 0.5-1 hour, a water-soluble initiator is added to set the third temperature for polymerization for a fourth time; after the reaction is completed, the polymer is filtered through a 100-300 mesh nylon filter to obtain a polymer composite emulsion.
3. The method according to claim 1, characterized in that: In (S11), the weight ratio of vegetable oil, neutralizer and catalyst is 10-40:1-6:0.1-2; the first temperature is 50-80°C; and the first time is at least 8 hours.
4. The method according to claim 1, characterized in that: In (S11), the vegetable oils include tung oil, rubber seed oil, olive oil, tung oil, castor oil, palm oil, soybean oil, linseed oil, linseed oil, sunflower oil, sunflower oil, coconut oil, cottonseed oil, safflower oil, safflower seed oil, tall oil, pine nut oil, rapeseed oil, corn oil, grape seed oil, peanut oil, hemp seed oil, perilla seed oil, poppy seed oil, sesame oil, canola oil, canola oil, algae oil, avocado oil, rice oil, shea butter, camellia oil, walnut oil, tomato seed oil, almond oil, apricot oil, cashew oil, nut oil, pistachio oil, walnut oil, nut oil, or any combination thereof; the neutralizer is N-methylethanolamine, triethylamine, diethylenetriamine, triethanolamine, or any combination thereof; the catalyst is sodium hydroxide, potassium hydroxide, sodium methoxide, catalytic ammonia water, or any combination thereof.
5. The method according to claim 1, characterized in that: In (S12), the weight ratio of the vegetable oil-based precursor to the acid anhydride is 10-40:4-25; the second temperature is 60-80° C.; and the second time is 8-12 hours.
6. The method according to claim 1, characterized in that: In (S21), the nanofibers are made of absorbent cotton, pulp, wood pulp, hemp, or any combination thereof; the water-soluble initiator is ammonium persulfate, potassium persulfate, a metal salt of peroxide, or any combination thereof.
7. The method according to claim 2, characterized in that: In (S22), the weight ratio of the vegetable oil-based acrylate monomer, the styrene monomer and the nanofiber suspension is 10-40:1-10:40-400; and the third time is 10-15 minutes.
8. The method according to claim 2, characterized in that: In (S23), the weight ratio of Pickering emulsion to water-soluble initiator is 40-80:0.2-0.4; the third temperature is 60-80°C; the room temperature is 25-35°C; and the fourth time is 2-4 hours.
9. A method for preparing a lithium battery separator by Pickering emulsion polymerization, comprising the following steps: (S3) Preparation of lithium battery separator: (S31) uniformly coating 1-3 parts of the Pickering emulsion or the polymer composite emulsion on the base film to form a membrane coating, drying the membrane coating at a fourth temperature, and drying for a fifth time to obtain a mixed membrane having heat resistance and adhesion, wherein: The Pickering emulsion is prepared according to the method of claim 1, and the polymer composite emulsion is prepared according to the method of claim 2.
10. The method according to claim 9, characterized in that: In (S31), the fourth temperature is 50-70°C; the fifth time is 0.5-2 minutes; and the base film is a PP base film or a PE base film.
Citation Information
Patent Citations
Acrylate adhesive modified by long-chain unsaturated carboxylic acid or derivative of long-chain unsaturated carboxylic acid and production method and application of acrylate adhesive modified by long-chain unsaturated carboxylic acid or derivative of long-chain unsaturated carboxylic acid
CN110627945A
CNF-stabilized styrene-acrylic emulsion as well as preparation method and application thereof
CN112745451A